Studies on the role of honey bees pollination in pomegranate (Punica granatum L.) (IASH Indian Journal of Arid Horticulture, 2026)
This study investigated the foraging activity of honey bees and other pollinators during the flowering period of pomegranate (Punica granatum). The highest foraging activity of honey bees was recorded under open conditions during the IV SMW, particularly between 12:00 to 14:00 hrs. Thirteen insect pollinator species were observed, with ants, butterflies, and beetles being the most abundant. Open pollination significantly outperformed other methods, including protected nylon net with bee cages, in promoting higher fruit set (65.60 fruits per plant), fruit length (81.16 mm), fruit diameter (78.09 mm), and fruit weight (280.40 g). Additionally, open pollinated plants showed the highest number of arils (601.40) and total soluble solids (16.92°Brix).